Implementation of the User Centered Design method on the Mobile Web - Yoyon Efendi; Muzawi, Rometdo; Rio, Unang; Saputro, Adi; Jamaris, Muhamad (JAIA - Journal of Artificial Intelligence and Applications, 2021)
The application of the User Centered Design (UCD) method is needed to improve the school website by redesigning it. The problems experienced by schools are usually in the form of a static website and an unattractive web appearance. This will be detrimental to the school, because the website is a door for information and school promotion. posting important news and announcements on the website in the hope that students and parents can obtain information more quickly and accurately. The UCD method starts from the plan, design, prototype and review. This step begins with interviews, field observations and distributing questionnaires to website users. Such as teachers, students, parents and the general public. The results provide a lot of input and optimize the appearance of mobile-based websites to attract more interest and better access by users. With the hope that students and parents can get information on news and important announcements more quickly and accurately on the website.